2008
DOI: 10.1103/physrevb.77.014406
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic and magnetic properties of the mixed-valence oxidesCaRu1xMnxO3

Abstract: The crystallographic and magnetic properties of CaRu 1−x Mn x O 3 ͑0 Յ x Յ 1.0͒ were investigated in detail by x-ray powder diffraction, magnetization, and magnetic Compton scattering measurements. The lattice parameters show considerable deviation from Vegard's law. Ferromagnetism appears at a relatively large Mn concentration ͑x Ն 0.2͒, and the magnetization and the Curie temperature have a maximum at a Mn content near x = 0.7. The magnetic Compton scattering measurement revealed that Mn makes a dominant con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
54
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(70 citation statements)
references
References 30 publications
16
54
0
Order By: Relevance
“…The data of CaRuO 3 could be refined by assuming an orthorhombic structure of the space group Pnma and the lattice constants of a ¼ 5.5324(4) Å , b ¼ 7.6640(5) Å , and c ¼ 5.3563(4) Å . These values agree well with those given in previous studies [4,[11][12][13]. The data of SrRuO 3 could be refined by assuming a cubic structure of the space group Pm3m and a lattice constant of a ¼ 3.9229(1) Å .…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…The data of CaRuO 3 could be refined by assuming an orthorhombic structure of the space group Pnma and the lattice constants of a ¼ 5.5324(4) Å , b ¼ 7.6640(5) Å , and c ¼ 5.3563(4) Å . These values agree well with those given in previous studies [4,[11][12][13]. The data of SrRuO 3 could be refined by assuming a cubic structure of the space group Pm3m and a lattice constant of a ¼ 3.9229(1) Å .…”
Section: Resultssupporting
confidence: 67%
“…SrRuO 3 is known as a metallic ferromagnet with a Curie temperature T C of 160 K, but no magnetic order could be found in CaRuO 3 at temperatures down to 0.3 K in spite of the negative asymptotic Curie temperature deduced from the data at high temperatures [1][2][3][4]. However, it has been reported that a very small substitution on the Ru site induced ferromagnetism in CaRuO 3 [5][6][7].…”
Section: Introductionmentioning
confidence: 89%
“…The possible coexistence of Ru 4+ , Ru 5+ , Mn 3+ , and Mn 4+ ions has been reported to explain the ferromagnetism observed in the CaRu 1Àx Mn x O 3 system. 13 Therefore, the ferromagnetism observed in the Ca 0.5 Sr 0.5 Ru 1Ày Mn y O 3 system should be attributed to the ferromagnetic exchange interaction between Mn 3+ and Mn 4+ ions. Moreover, a magnetic Compton scattering study on the CaRu 1Àx Mn x O 3 system revealed that the Mn spin moments are antiparallel to the Ru spin moments and that Mn makes a dominant contribution to the magnetization.…”
Section: Resultsmentioning
confidence: 97%
“…This behavior has been explained assuming a mixed-valence state of Ru 4+ , Ru 5+ , Mn 3+ , and Mn 4+ ions. 13 Figure 2a shows the temperature dependence of the magnetization measured for specimens of Ca 0.5 Sr 0.5 Ru 1Ày Mn y O 3 (0 £ y £ 1.0) under an applied field of 1 kOe. The thermomagnetic curves M(T) of specimens with low Mn content (x < 0.2) show ferromagnetic behavior with lower T C , near 50 K. The ferromagnetism of the specimens with low Mn content seems to originate due to a mechanism similar to that of the ferromagnetism in SrRuO 3 .…”
Section: Resultsmentioning
confidence: 99%
“…6 It is therefore not surprising that perovskites which contain both Mn and Ru have also attracted considerable interest. [7][8][9][10][11][12][13][14][15] The physical properties of these compounds are primarily governed by the oxidation states of the Mn and Ru cations, which often exist in a state of mixed valency. The properties of these materials can be tuned by controlling the ratio of Mn to Ru and also by manipulating the charge and/or size of the cations on the A-site.…”
Section: Introductionmentioning
confidence: 99%